Higher Education Quality Management: Evidence from Adrar University - Houcine, Benlaria; Sofiane, Mostéfaoui (Asian Journal of Economic Modelling, 2018)
The quality of education seems to be one the biggest challenges that face the educational institutions, in particular the University ones. This issue prompted many of them to adopt total quality management concepts in order to raise the level of teaching and learning and a focus on the quality of its output efficiency. Therefore, this study aims to examine the reality of the comprehensive quality management at the University of Adrar. The opinions of professors and students of Adrar University had been analyzed, and in light of that study, we conclude that there is no comprehensive quality at the level of this university.